Pengaruh Rasio Keuangan terhadap Perubahan Laba Bersih pada Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Feberwin Telaumbanua; Ardianus Lau; Geoger F Sitorus; Faliza Fasya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of financial ratios on changes in net income in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The variables examined include CR, QR, ROA, ROE, DER, and TAT. The method used is multiple linear regression with classical assumption tests. The results indicate that ROA, ROE, and TAT have a significant positive effect, while DER has a significant negative effect on changes in net profit. CR and QR do not have a partial effect. Simultaneously, all variables have a significant effect with an R² of 68.1%. These findings emphasize the importance of efficiency and profitability in driving profit growth.